Electrical and Electromagnetic Interference (EMI) shielding properties of hexagonal boron nitride nanoparticles reinforced polyvinylidene fluoride nanocomposite films. Issue 11 (24th July 2019) - Sankaran, Sowmya; Deshmukh, Kalim; Ahamed, M. Basheer; Sadasivuni, Kishor Kumar; Faisal, Muhammad; Pasha, S. K. Khadheer
ABSTRACT: The hexagonal boron nitride nanoparticles (h-BNNPs) reinforced flexible polyvinylidene fluoride (PVDF) nanocomposite films were prepared via a simple and versatile solution casting method. The morphological, thermal and electrical properties of h-BNNPs/PVDF nanocomposite films were elucidated. The electromagnetic interference (EMI) shielding properties of prepared nanocomposite films were investigated in the X-band frequency regime (8–12 GHz). The EMI shielding effectiveness (SE) was increased from 1 dB for the PVDF film to 11.21 dB for the h-BNNPs/PVDF nanocomposite film containing 25 wt% h-BNNPs loading. The results suggest that h-BNNPs/PVDF nanocomposite films can be used as lightweight and low-cost EMI shielding materials. GRAPHICAL ABSTRACT: